2017
DOI: 10.5751/es-09084-220146
|View full text |Cite
|
Sign up to set email alerts
|

A comparative appraisal of the resilience of marine social-ecological systems to mass mortalities of bivalves

Abstract: ABSTRACT. In many parts of the world, both wild and cultured populations of bivalves have been struck by mass mortality episodes because of climatic and anthropogenic stressors whose causes and consequences are not always clearly understood. Such outbreaks have resulted in a range of responses from the social (fishers or farmers) and governing systems. We analyzed six commercial bivalve industries affected by mass mortalities using I-ADApT, a decision support framework to assess the impacts and consequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…This effect has been observed in the Uruguayan seafood sector, where increasing imports are leading the sector into an economic crisis. 65 In some cases, impacts can result in the relocation of processing facilities, markets, or fishing vessels. International fish markets have been seen as a buffer to local supply shocks, but reliance on international trade can have negative effects, such as the loss of domestic products and the vulnerability of jobs to price and supply shocks elsewhere.…”
Section: Llmentioning
confidence: 99%
“…This effect has been observed in the Uruguayan seafood sector, where increasing imports are leading the sector into an economic crisis. 65 In some cases, impacts can result in the relocation of processing facilities, markets, or fishing vessels. International fish markets have been seen as a buffer to local supply shocks, but reliance on international trade can have negative effects, such as the loss of domestic products and the vulnerability of jobs to price and supply shocks elsewhere.…”
Section: Llmentioning
confidence: 99%
“…These mass mortalities may reflect a marine disturbance and thus damaged health of the marine coastal ecosystem (Sherman, 2000). Additionally, these recurrent mortalities cause an imbalance in the entire coastal socio‐ecosystem, and stakeholders need to adapt permanently to ensure the sustainability of their socio‐economic activities (Guillotreau et al, 2017). Representative bodies of the shellfish industry often alert the government authorities about these sustainability concerns, asking either for research to be conducted to explain these mass mortality events and to mitigate the outbreaks, or for financial compensation to mitigate their effects on socio‐economic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Among studies that analyzed both systems relatively equally, we found that Berkes (2011), Broderstad and Eythórsson (2014), Cullen-Unsworth et al (2014), Engie and Quiroga (2014) analyzed the mutual influences of both systems, which can strengthen SES modeling (Davies et al, 2016;Melbourne-Thomas et al, 2017). Others (Glaser et al, 2012;Perry and Masson, 2013;Guillotreau et al, 2017;Hu et al, 2018;Li et al, 2018;Peña-Alonso et al, 2018) used indicators that integrated variables representing the social and ecological systems. For instance, Perry and Masson (2013) constructed indicators identifying changes in large-scale temporal patterns of variability in the Strait of Georgia.…”
Section: Inclusion Of Socio-ecological System Componentsmentioning
confidence: 96%